Rise and decline of the land planarian genus Geoplana (Platyhelminthes: Tricladida) - Fernando Carbayo (Zoologia (Curitiba))
ABSTRACT A taxonomic history of Geoplana, one of the most popular names for land planarians, is presented. The number of species within the genus has varied significantly since its unnoticed establishment in 1847. The number rose to 339 species in the 1980s before declining to 61 species, including 48 species incertae sedis. Eight diagnoses of Geoplana have since been proposed, resulting in the inclusion or removal of species. Accordingly, the genus underwent changes in its geographic range, expanding to encompass several continents in 1899 but ultimately being reduced to its current presence in Southeast Brazil. The genus is considered monophyletic, though it still houses 48 species incertae sedis. To better understand Geoplana, it is necessary to reassess the taxonomic status of these 48 species and describe several undescribed species.